The Influence of Story Pyramid Strategy towards Students’ Reading Ability of Narrative Text - Nurchurifiani, Eva (English Education: Jurnal Tadris Bahasa Inggris, 2018)
The objective of this research are to know whether there is a positive influence of story pyramid strategy towards students’ reading ability of narrative text , and to know whether the average score of students’ reading ability of narrative text who learned reading through story pyramid strategy higher than those who learn reading through conventional technique.The research was conducted at the eighth grade of SMP Negeri 19 Pesawaran. The research used the experimental method. The population of the research was taken from the students at the second semester at the eighth grade of SMP Negeri 19 Pesawaran in academic year 2016/2017.This research used cluster random sampling technique to took the sample.The researcher took two classes as the sample. The first class as experimental class. It was VIII A and the second class as control class. It was VIII B class.In analyzing the data used t–test formula.Based on the data analysis and hypothesis test,it found that the result of calculating was t-test (4.91) with t-table (2,00) so, Ho was refused. It means that there is possitive infuence of teaching reading through story pyramid strategy.And the average score of students’ reading ability who learn reading through story pyramid strategy is higher than who learn reading through conventional technique. The average score of experimental class was57,79 and Control class was46.39. So, there was influence of story pyramid strategy towards students’ reading ability of narrative text at the eight grade of SMP Negeri 19 Pesawaran.